Exploring teacher design team endeavors while creating an elementary-focused STEM-integrated curriculum - Justin R. McFadden; Gillian H. Roehrig (SpringerOpen, 2017)
Abstract Background This study presents two teacher design teams (TDTs) during a professional development experience centered on science, technology, engineering, and mathematics (STEM)-integrated curriculum development. The main activity of the study, curriculum design, was framed as a design problem in order to better understand how teachers engaged with the complexities of integrated curriculum development. Additionally, Remillard's, (Review of Educational Research 75:211-246, 2005) teacher-curriculum "participatory relationship" provided a framework for further exploring teacher actions during the design process. Utilizing a case study research design, participant curriculum design conversations were audio-recorded for 12 days during a summer professional development experience. Constructed grounded theory and a method of selective coding revealed insights about the processes and supports that enable collaborative curriculum design. Results Results showed that when a TDT is not prompted and/or enabled to first lay out and articulate the overall value of a STEM-integrated curriculum, they will rightly follow their intuitions as classroom teachers and engage in the process accordingly. Second, involving practicing teachers in the curriculum design process requires complete "participation" with the curriculum ideas they are contemplating because in the end, the curriculum's resultant lessons will be taught in their own and other teacher's classrooms. Conclusions The findings from this study indicate the importance of "pushing" active classroom teachers from the design to the mapping arena by instituting curriculum development activities and/or strategies (i.e., processes) that might help a TDT develop a "voice" (Remillard, From Text to 'Lived' Resources:105-122, 2011) or "value" (Dorst, Design Studies 22:4-17, 2006) for the curriculum under development. If members of a TDT are willing to reveal their interpretations, perceptions, and beliefs about the conceptual ideas embedded within the curriculum being developed, both the teachers and curriculum being developed will benefit. Finally, teachers should be made aware of their roles and responsibilities, beyond superficial descriptions; and understand participation in STEM-integrated curriculum design brings with it the likelihood their individual ideas, perceptions, and beliefs will be integrated within the curriculum being developed.